Rapid Visual Detection of Decapod Iridescent Virus 1 ( DIV1 ) by RPA Combined With LFS - Quanling Mu; Cunbao Ding; Ying Xie; Xi Zhen; Xianrui Wang; Tongaobo Qi; Jiaming Zhang; Yakun Yu (Journal of Fish Diseases, 2026)
Decapod iridescent virus 1 (DIV1) causes severe disease outbreaks in shrimp and crab culture areas. A simple, rapid, and visual DIV1 assay is important for the control of viral diseases. This study presented a novel DIV1 detection method that combines recombinase polymerase amplification (RPA) and lateral flow strip (LFS). After selecting primers and probes, we optimised the concentration of the reverse primers, reaction time, as well as reaction temperature of RPA‐LFS detection. RPA can amplify the target gene within 18 min at a constant temperature of 38°C, and LFS can observe the amplification results within 3 min. Importantly, there is no cross‐reactivity with other infectable shrimp viruses and pathogens, such as WSSV, IHHNV, TSV, EHP, CMNV, YHV, MrNV samples, as well as Vp AHPND . In addition, RPA‐LFS has high detection sensitivity, with a lower detection limit of 1.12 × 10 1 copies/μL. Using 110 field samples, the results of qPCR recommended by WOAH (OIE) and RPA‐LFS were identical, indicating that RPA‐LFS is as reliable as qPCR. The RPA‐LFS assay is a valuable tool for the rapid and accurate detection of DIV1.